The student's guide to preparing dissertations and theses - Allison, Brian, 1931- (Routledge study guides., 2004)
When writing a dissertation or thesis, it is essential to produce a work that is well-structured and well-presented. Giving clear examples throughout, this book offers all the practical advice that students will need, when writing a dissertation or thesis. Part 1: Content - from the layout order of contents to the compilation of the bibliography and appendicesPart 2: Presentation and Style - the details of how work should be presented and covering aspects such as writing styles, page numbers, margins and abbreviations. The first edition of this book contributed to improving countless dissertatio.